International Fragmentation of Value-added Chains: How Does it Affect Domestic Factor Prices? - Wilhelm Kohler (University of Copenhagen, Economic Policy Research Unit (EPRU), 2001)
Economic globalization causes an increasing international fragmentation of value-added chains. A question often raised is whether such outsourcing affects domestic income distribution. The paper provides a theoretical treatment of this issue within a Heckscher-Ohlin framework. It extends beyond previous treatments by allowing for an arbitrary number of goods, factors, and fragments, and by formally specifying a fragmentation technology. It defines a margin of international fragmentation and shows how this margin shifts in response to economic globalization. Factor prices are driven by associated changes in effective prices of individual fragments of the value-added chains.
Keywords: 330